Pemodelan Peak Ground Accleration (PGA) dan Intensitas Gempabumi berdasarkan Pengukuran Mikrotremor pada Kawasan Longsor di Desa Kalongan, Ungaran Timur - Nugroho Budi Wibowo; Thaqibul Fikri Niyartama; Andi Andi; Rena Septiana; Erlina Widianingrum; Ahdian Azri Bustari; Iktifal Ajie Arif (Universitas Andalas, 2024)
The landslide in Kalongan Village affected an area of 5 hectares and has the potential to experience further landslides. Landslides can occur with triggers of external factors such as earthquakes. The Peak Ground Acceleration (PGA) parameter can represent the impacts that occur on the surface in the form of earthquake intensity (MMI). Kalongan Village is 25.5km from the epicenter of the Ambarawa earthquake on 27 May 2023. This study aims to modeling the PGA microzonation and the intensity of the Ambarawa earthquake in the avalanche zone in Kalongan Village. The PGA model is based on measurements of 72 microtremor data in the avalanche zone using the Kanai method. Parameters of the Ambarawa earthquake with a magnitude of 2.5 and a depth of 5 km. The results of PGA modeling in the avalanche zone varied between 1.0-7.1 gal or I-II MMI values. The results of the PGA modeling show that aftershocks can occur if the strength of the Ambarawa earthquake reaches M=4 or 7.1-50.8 gal. The strength of the earthquake is equivalent to the intensity of II-V MMI.